Self-concept and body image of people living with lupus: A systematic review - Rodrigues, Larissa (2021)
Aim: To summarize existing evidence regarding body image in patients with systemic lupus erythematosus, with the following considerations: (a) the perceptions patients have of their body changes; (b) how patients cope with changes in their body; (c) and what their perceptions are of body changes. Method: A systematic review of literature integrating quantitative and qualitative studies. We searched databases (PubMed, CINAHL, Embase, SCOPUS, the Web of Science, Medline, Medline Complete, and Academic Search Premier) and publications from 2010 to 2020 with “Systemic Lupus Erythematosus” AND “Self-Concept” OR “Body Image” AND “Woman” as medical subheading terms. The studies included were subjected to a thematic content analysis, which allowed subjective interpretation of data through a systematic classification process for coding themes or patterns. Results: We identified 647 studies, of which 22 were analyzed in this study. Our results indicate that changes in the body image of people with lupus and their perception are issues that must be treated as characteristics of the disease; therefore, they need to receive the same attention as is given to physical disabilities and pain. The analysis identified 3 thematic categories: (a) depression and anxiety associated with body changes (hair loss, weight gain); (b) body image reflecting the disease; and (c) confrontations and interventions to promote acceptance and adaptation to the new image. Conclusions: The dimensions of self-concept and body image are essential for assessing the quality of life of individuals with lupus. The formation of a adjusted selfconcept can be managed by health professionals supporting these people.